2010
DOI: 10.1021/la1020687
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Double-Layer, van der Waals, and Polymer Depletion Attraction Forces between Supported Cationic Bilayers

Abstract: The interactions of supported cationic surfactant bilayers and the effects of nonadsorbing cationic polyelectrolytes on these interactions were studied using the surface forces apparatus (SFA) technique. Bilayers of the cationic surfactant di(tallow ethyl ester) dimethyl ammonium chloride (DEEDMAC) were deposited on mica surfaces using the Langmuir-Blodgett technique, and the interactions between the bilayers were measured in various salt, nonionic polymer (PEG), and cationic polyelectrolyte solutions at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 48 publications
7
42
0
Order By: Relevance
“…To implement our model, we require the values of WP(0) and K a . A recent SFA study51 shows that the interactions between the cationic surfactant under study in the presence of polyDADMAC are well represented by a combination of van der Waals attraction, a modified electrostatic repulsion and the depletion-induced attraction. The calculations are identical to those presented in section 2.2, except that the electrostatic repulsion term has to be modified according to the approach of Tadmor et al 52.…”
Section: Resultsmentioning
confidence: 99%
“…To implement our model, we require the values of WP(0) and K a . A recent SFA study51 shows that the interactions between the cationic surfactant under study in the presence of polyDADMAC are well represented by a combination of van der Waals attraction, a modified electrostatic repulsion and the depletion-induced attraction. The calculations are identical to those presented in section 2.2, except that the electrostatic repulsion term has to be modified according to the approach of Tadmor et al 52.…”
Section: Resultsmentioning
confidence: 99%
“…We surmise that crowding effects are triggered by the increase in overall volume fraction and/or by polymer induced depletion interactions [38,39]. Adding polymers to a colloidal dispersion is known to induce short-range attractive forces between particles above a threshold volume fraction [42,43]. It is also possible that other interaction types are present and also modify the vesicular organization.…”
Section: Iii13 -Effect Of Guars On the Vesicle Structure In Formulamentioning
confidence: 86%
“…DLVO theory can describe the interaction between vesicles in a dilute solution. [17][18][19] However, in a concentrated dispersion in the presence of polymer additives, no simple theory can accurately determine the interaction between vesicles. In the presence of adsorbing or non-adsorbing polymers, combined effects due to DLVO forces, steric repulsion, depletion attraction, hydration and hydrophobic forces, and forces due to mechanical deformation of the vesicle surface may all contribute to the overall interaction potential.…”
Section: 10mentioning
confidence: 99%
“…19 The effect of non-adsorbing charged and uncharged polymers on the forces between bilayers were explored experimentally. 19 Simulation of polymer graed lipid bilayers were performed 26 and experimental evidence of hydrophobic interaction between the protein molecules and lipid domains were investigated by X-ray diffraction technique. 8 The latter work showed that proteins and polymers adsorb to bilayer surfaces and causes an increase in the head group area of the lipid molecules while collapsing the thickness of the bilayer membrane, still maintaining the bilayer integrity.…”
Section: 10mentioning
confidence: 99%
See 1 more Smart Citation